A Survey on Understanding of the Matilda Effect Among Guangzhou International High School Students - Liu, Dongxin; Li, Yuxuan (Journal of Education, Humanities and Social Sciences, 2025)
This paper reports on the execution and efficacy of a dual-mode physical exhibition and social media campaign for raising high school student awareness of the Matilda Effect and women scientists’ contributions through international communication. The intervention was implemented through a 10-day exhibition with some interactive elements and coordinated content on the WeChat platform. Awareness and understanding regarding students were both tested using the post- and pre-intervention questionnaires, student interviews, and some engagement metrics. Knowledge of the Matilda effect increased from 37.5% to 100% within the target population, with 91.42% being exposed to educational materials and 77.14% of those achieving a clear understanding. The WeChat platform saw 248 unique viewers at its peak engagement time, which was during after-school hours (from 4 to 6 p.m.). The physical exhibition drew approximately 300 visitors and elicited just over 50 reflective student comments. These findings prove that blending traditional formats of exhibitions with social media platforms can effectively engage students in discussion on gender bias concerning scientific recognition. This offers a model that can be followed when similar issues need to be addressed in science education.